The Influence Of Motivation And Work Environment On Employee Performance In Plaza Toyota, Green Garden Branch - Helmi Helmi; Richardus Risky Ratrigis; Nurwati Nurwati (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2021)
The purpose of this study was to determine the effect of providing motivation and work environment on employee performance at Plaza Toyota Green Garden Branch, in accordance with the indicators set forth in the theory. The values ​​tested in this thesis use the Quantitative Associative testing formula. The results of the validity test of Motivating Variables (X1) get the results with the number 0.425, then the rcount 0.425> rtable 0.279 is declared valid and the Work Environment variable (X2) gets the result with the number 0.404 which means valid because the rcount is 0.404> rtable 0.279. Followed by multiple linear regression tests that produce constants of 1,775 which means there is a positive significance of providing motivation and work environment on employee performance with the equation Y = 1.775 + 0.462 (X1) +0.448 (X2). From the results of the coefficient of determination test conducted, obtained KD = 0.333 or 33.3% means that 33.3% employee performance is influenced by providing motivation (X1) and work environment (X2), the remaining 66.7% is influenced by other variables that are not included in this study. Besides that, from the F test results, an F value of 3.20 was obtained using the F distribution table and a significance level of 0.005, then a Ftable of 3.20 was obtained. So it can be seen that Fcount> i.e. 11,715> 3.20. Means that Ho is rejected and Ha is accepted, so that there is a significant influence between the Provision of Motivation and the Work Environment on employee performance at Plaza Toyota Green Garden Branch